2022
DOI: 10.1136/bmjdrc-2021-002703
|View full text |Cite
|
Sign up to set email alerts
|

First trimester plasma microRNAs levels predict Matsuda Index-estimated insulin sensitivity between 24th and 29th week of pregnancy

Abstract: IntroductionGestational diabetes mellitus (GDM) is a consequence of an imbalance between insulin sensitivity (IS) and secretion during pregnancy. MicroRNAs (miRNAs) are small and secreted RNA molecules stable in blood and known to regulate physiological processes including glucose homeostasis. The aim of this study was to identify plasmatic miRNAs detectable in early pregnancy predicting IS at 24th-29th week of pregnancy.Research design and methodsWe quantified circulating miRNAs in 421 women in plasma collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Regarding year of publication, 3.33% of the articles were published in 2013 [ 1 ], 2014 [ 19 ], or 2015 [ 13 ], and 6.67% of the reports were published in 2016 [ 22 , 23 ] and 2019 [ 2 , 12 ]. In addition, 10% of the studies were published in 2017 [ 4 , 24 , 25 ] and 2018 [ 15 , 21 , 26 ], while 13.33% of the articles were published in 2021 [ 3 , 8 , 14 , 17 ] and 2022 [ 6 , 10 , 27 , 28 ]. Finally, 30% of the studies were published in 2020 [ 5 , 7 , 9 , 11 , 16 , 18 , 20 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding year of publication, 3.33% of the articles were published in 2013 [ 1 ], 2014 [ 19 ], or 2015 [ 13 ], and 6.67% of the reports were published in 2016 [ 22 , 23 ] and 2019 [ 2 , 12 ]. In addition, 10% of the studies were published in 2017 [ 4 , 24 , 25 ] and 2018 [ 15 , 21 , 26 ], while 13.33% of the articles were published in 2021 [ 3 , 8 , 14 , 17 ] and 2022 [ 6 , 10 , 27 , 28 ]. Finally, 30% of the studies were published in 2020 [ 5 , 7 , 9 , 11 , 16 , 18 , 20 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, subsequent large-scale investigations are required to evaluate the positive predictive value, specificity, and sensitivity of C19MC microRNAs for hypertension or pre-eclampsia. The effectiveness of placental-specific microRNAs for diagnosing disease severity should be assessed in connection with Doppler ultrasonography characteristics, delivery needs, and clinical symptoms [ 10 ]. The research produced intriguing results, showing that up-regulation of circulating C19MC microRNAs is a hallmark of early pregnancy, which is predisposed to developing issues linked to gestational hypertension and placental insufficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another previous study from our group and using the same Gen3G microtranscriptomic dataset, we identified miRNAs in the first trimester of pregnancy associated with and predictive of insulin sensitivity in the second trimester of pregnancy. Among our replicated miRNAs, 15 were also associated with insulin sensitivity [ 17 ]. Similar analyses were also conducted to identify miRNAs associated and predictive of GDM still using this microtranscriptomics and Gen3G datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, miRNAs are suspected of having an important role in pregnancy, its maintenance as well as adaptation to its very specific physiologic needs [ 10 , 11 ]. Accordingly, dysregulation of the C19MC and C14MC has been associated with pregnancy complications, including PE, intrauterine growth restriction and insulin sensitivity regulation [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%